Retrospective Study of Skin Prick Test in Atopic Dermatitis Patients at DermatoVenereology Outpatient Clinic of Dr. Soetomo General Hospital Surabaya During 2007-2012 - Natallya, Fransiska Rismauli; Barakbah, Jusuf (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2015)
Background: Atopic dermatitis (AD) gives impact on quality of life of patients because ofÂ  frequent exacerbation. Various factors play a role in pathogenesis of AD. Trigger factors of exacerbation especially due to enviroment including irritant and allergen agents. Identifying and avoiding trigger factors are important in management of AD. Skin prick test (SPT) is one method to detect the presence of Ig E spesiï¬c to certain allergens (food allergens, aeroallergens). Purpose: To describe the characteristic of AD patients, and evaluate the result of SPT and their clinical relevance. Methods: This research was a retrospective study of AD patients who underwent SPTÂ  during 2007-2012. Results: Nineteen of 57 patients (33,3%) had positive SPT to one or more allergens, and 36 patients (63,1%) had negative result. One patient (1,8%) showed false positive result and 1 patient (1,8%) showed false negative result. The most common allergens were house dust in 8 patients (42%) and crab in 6 patients (31,6%). Clinical relevance was found in 11 patients (58%), and 8 patients (42%) had no clinical relevance. Compared with SPTânegative patients, SPTâpositive patients showed more severe symptom and clinical manifestation. Conclusions: In this study, the allergens could be detected in 19 patients (33,3%) by SPT, mostly to house dust (42%) and crab (21,6%). Clinical relevance was found in 11 patients (58%). SPT is recomended to perform in management of AD in order to detect enviromental allergen because it has signiï¬cant clinical relevance.Â Key words: atopic dermatitis, skin prick test, allergens.